DNA Damage and Base Excision Repair in Mitochondria and Their Role in Aging - Ricardo Gredilla (Journal of Aging Research)
During the last decades, our knowledge about the processes involved in the aging process has exponentially increased. However, further investigation will be still required to globally understand the complexity of aging. Aging is a multifactorial phenomenon characterized by increased susceptibility to cellular loss and functional decline, where mitochondrial DNA mutations and mitochondrial DNA damage response are thought to play important roles. Due to the proximity of mitochondrial DNA to the main sites of mitochondrial-free radical generation, oxidative stress is a major source of mitochondrial DNA mutations. Mitochondrial DNA repair mechanisms, in particular the base excision repair pathway, constitute an important mechanism for maintenance of mitochondrial DNA integrity. The results reviewed here support that mitochondrial DNA damage plays an important role in aging.